Wittgenstein : a religious point of view? - Malcolm, Norman, 1911-1990 (Routledge, 1993)
Ludwig Wittgenstein once said: 'I am not a religious man, but I cannot help seeing every problem from a religious point of view.' This study, the last work of the distinguished philosopher Norman Malcolm, is a discussion of what Wittgenstein may have meant by this and its significance for philosophy. The book concludes with a critical discussion of Malcolm's essay by Peter Winch.